2016
DOI: 10.1016/j.jmgm.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation into the interactions between murine 5-HT3 receptor and the principle active compounds of ginger (Zingiber officinale)

Abstract: . In silico investigation into the interactions between murine 5-HT3 receptor and the principle active compounds of ginger (Zingiber officinale).. Retrieved from http://dx.doi. org/10.1016/j.jmgm.2016.10.008 1 Abstract Gingerols and shogaols are the primary non-volatile actives within ginger (Zingiber officinale).These compounds have demonstrated in vitro to exert 5-HT3 receptor antagonism which could benefit chemotherapy-induced nausea and vomiting (CINV). The site and mechanism of action by which these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…All binding poses of capsazepine are located at the interface between transmembrane domain (TMD) and extra cellular domain. This binding site is situated in similar position with allosteric binding site predicted by ( Lohning et al, 2016 ). Free energy of binding predicted by Autodock Vina for most favorable docking pose is −7.8 kcal/mol.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…All binding poses of capsazepine are located at the interface between transmembrane domain (TMD) and extra cellular domain. This binding site is situated in similar position with allosteric binding site predicted by ( Lohning et al, 2016 ). Free energy of binding predicted by Autodock Vina for most favorable docking pose is −7.8 kcal/mol.…”
Section: Resultssupporting
confidence: 77%
“…Grid center was designated x, y, z dimensions: 139.00, 219.00 and 273.00. These coordinates correspond to allosteric binding site of 5HT 3 receptor for ginger compounds identified in an earlier study ( Lohning et al, 2016 ) on human 5HT 3 receptor. Docking calculations were performed using the Lamarckian genetic algorithm (LGA) ( Morris et al, 1998 ).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…As a consequence, this process reduces the 5-HT 3A blocking activity of ginger [57]. Although all data showed that ginger-derived molecules act allosterically, in silico techniques showed that these compounds can also bind to the orthosteric binding site causing competitive inhibition as well [110]. Ginger extracts were also tested against other ion channels such as L-type Ca 2+ , Na + and K + channels.…”
Section: Natural Negative Allosteric Modulators Of 5-hydroxytryptamentioning
confidence: 99%
“…Also, gingerols and shangols could interact with the human serotonin 5‐HT 1A receptor with moderated binding affinities (Ki = 3–20 μM), suggesting a partially agonist for this receptor (Nievergelt, Huonker, Schoop, Altmann, & Gertsch, ). Moreover, ginger compounds have demonstrated in vitro 5‐HT 3 receptor antagonism (Lohning, Marx, & Isenring, ). It is widely known that activation of the 5‐HT 3 receptor produced a pronociceptive effect (Hoyer et al, ).…”
Section: Introductionmentioning
confidence: 99%